2020
DOI: 10.1166/jmihi.2020.2968
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition Protocols to Optimize 68Ga-DOTA-NOC Position Emission Tomography/Computer Tomography Image Quality Based on Patient Body Mass Index and Injected Dose

Abstract: Background: The choice of 68Ga-DOTA-1-Nal3-octreotide (68Ga-DOTA-NOC) injected dose and Position emission tomography/computer tomography (PET/CT) acquisition time is still a challenge for obtaining consistently high-quality PET image. Objective: To determine the optimal acquisition protocols based on patient body mass index (BMI) and the injected dose per kilogram for 68Ga-DOTA-NOC PET/CT imaging. Patients and Methods: This was a retrospective analysis of 51 patients (21 males and 30 females) who underwent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In addition, further increasing penalization factor might produce smoother images, but result in less contrast enhancement, pointing out that this noise level should be considered as the target noise setting for acquiring high quality images in 68 Ga-DOTA-NOC PET/CT practice. This phenomenon was consistent with previous studies using BPL algorithm on 68 Ga tracer PET with high penalization factor [12,18] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, further increasing penalization factor might produce smoother images, but result in less contrast enhancement, pointing out that this noise level should be considered as the target noise setting for acquiring high quality images in 68 Ga-DOTA-NOC PET/CT practice. This phenomenon was consistent with previous studies using BPL algorithm on 68 Ga tracer PET with high penalization factor [12,18] .…”
Section: Discussionsupporting
confidence: 93%
“…Minor change of average normalized SUV max was found for large lesions in all HYPER iterative groups, and the minor change was also found for the medium lesions. The mean of normalized SUV max was higher than research and PET detection performance [12] . The mean of normalized SUV max for high injected activity groups was slightly higher than that for low injected activity in all HYPER iterative groups except for HR2.3-H2.5 (Figure 3b).…”
Section: Quantitative Analysis Of Clinical Studymentioning
confidence: 61%
“…By current procedure guidelines, the recommended activity of for 68 Ga-DOTA-conjugated peptides ranges from 100 to 300 MBq depending on the PET imaging characteristics [ 16 , 17 ]. Our data showed that, regardless of the injected activity per kilogram, HYPER Iterative had a higher lesion SUV max than OSEM, but the penalization factor had a limited influence on the increase in lesion SUV max between HYPER Iterative groups with the same acquisition time, and the lesion SUV max increased slightly as acquisition time was increased from 2 m/b to 3 m/b.…”
Section: Discussionmentioning
confidence: 99%
“…In the image acquisition and processing system, the system design usually follows three design modes: hardware acquisition and software processing mode, separated hardware acquisition and processing mode and integrated hardware acquisition and processing mode. The three schemes have their own characteristics and are suitable for different occasions [1] . Video is a vivid description of objective things, an intuitive and concrete form of information expression, and the most important information carrier of human beings.…”
Section: Introductionmentioning
confidence: 99%